"Mentality Box Futurakit" as Psychological First Aid To Rescue Sandwich Generation from Suicide Ideation - Alifia, Kayla Naifah; Nur, Nurul Kamilah Bennu; Zulchairani, Asviannisa Rachma; Wulaningrum, Dita Sari; Pranungsari, Dessy (Proceedings of The International Conference on Psychology and Education, 2024)
In contemporary society, suicidal ideations are a relatively common occurrence and are not often considered unusual or infrequently discussed. The prevalence of suicide remains a concern, as indicated by recent data showing 287 reported cases in Indonesia. Particularly noteworthy is the Special Region of Yogyakarta, which ranks third nationwide for suicidal ideation instances. This research employs a quantitative and experimental method with a quasi-experimental design, specifically utilizing the one-group pre-test and post-test design. The study included 12 participants who were current students at different universities in Yogyakarta. The criteria for selection included active student status and being part of the sandwich generation, as well as having experienced suicidal thoughts. The collection of data utilized the Suicidal Behaviors Questionnaire-Revised (SBQ-R) scale. The data was assessed using Wilcoxon analysis with SPSS 23.0 for Windows. The analysis results indicated a Z score of -2.251, with a significance level of 0.024 (p < 0.05), suggesting a significant difference in the subjects' pre-test and post-test results before and after administering the intervention. Therefore, the study determined that the subject's suicidal thoughts were encapsulated in nine thematic findings, and the effectiveness of the "Mentality Box Futurakit" in alleviating suicide ideation in the subject was confirmed.